Psychological Features of Interpersonal Communication in Youth Students - Tryhub, Halyna (International University of Applied Sciences in Lomza, 2025)
The article describes that the rapid development of scientific and technical progress, globalization and urbanization of the world, the lack of stability in the political and economic spheres of society, and the imposition of desired attitudes and patterns of behavior by society affect the specifics of human functioning in the social environment and acutely pose the problem of personal communication. Communication is one of the most important phenomena that supports various forms of human relations, forms various social relations, and develops an individual's psychological features. The structure of communication is considered as a connection of interrelated factors: communicative (exchange of information between individuals), interactive (organization of interaction between communication participants, i.e. exchange of not only knowledge, ideas, but also actions), wise (the process of perception and recognition by partners of each other and establishing mutual understanding on this basis).
Keywords: Interpersonal Communication; Personality; Personality Orientation; 316.6:316.47-057.875